ANALISIS KINERJA SAHAM PERUSAHAAN SETELAH MELAKUKAN INITIAL PUBLIC OFFERING DIBURSA EFEK JAKARTA - Ruqayyah Ruqayyah; Nur Hidayati; Mohammad Amin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis was an event study on the performance of stocks after the companyconducted an IPO on the BEI. The goal is to find out what happened phenomenonoutperformed short-tram stock performance to what happened three months andunderperformed the phenomena of long-term stock performance for two years.Performance is measured by stock return. The samples were companies in IPOperiod 2014-2015. A total of 38 companies.The result of this study indicate that short-term phenomena three month alsooutperformed the stock performance indicated by positive return of 23,684% And forthe long-term phenomena occurred two years also outperformed the stockperformance indicated by positive return of 35,459%. The performance increase wassignificant, the results of both studies support previous that long-term not phenomenaunderperformed.Keyword: company growth after IPO, experiencing an increase or decrease